2020
DOI: 10.1101/2020.02.12.945220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic flexibility allows generalist bacteria to become dominant in a frequently disturbed ecosystem

Abstract: Ecological theory suggests that habitat disturbance differentially influences distributions of generalist and specialist species. While well-established for macroorganisms, this theory has rarely been explored for microorganisms. Here we tested these principles in permeable (sandy) sediments, ecosystems with much spatiotemporal variation in resource availability and other conditions. Microbial community composition and function was profiled in intertidal and subtidal sediments using 16S amplicon sequencing and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 82 publications
(86 reference statements)
2
16
1
Order By: Relevance
“…This is in line with previous studies that showed Woeseiales is an abundant lineage in marine sediments worldwide [7,12,13], although the properties that determine such ecological success are poorly understood. Previous work has suggested metabolic plasticity to be at the root of the global distribution and high abundance continuously observed for Woeseiales worldwide [7,13,15]. Our high-resolution transcriptional evidence supports this idea and suggests that the Woeseiales in these Arctic fjords are able to sense and adapt to their environment upon burial, most likely in response to changes in redox chemistry.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is in line with previous studies that showed Woeseiales is an abundant lineage in marine sediments worldwide [7,12,13], although the properties that determine such ecological success are poorly understood. Previous work has suggested metabolic plasticity to be at the root of the global distribution and high abundance continuously observed for Woeseiales worldwide [7,13,15]. Our high-resolution transcriptional evidence supports this idea and suggests that the Woeseiales in these Arctic fjords are able to sense and adapt to their environment upon burial, most likely in response to changes in redox chemistry.…”
Section: Discussionsupporting
confidence: 85%
“…This supports the idea that different populations of Woeseiales may have fundamentally different physiologies. Even single representatives of Woesiales have been hypothesized to be metabolic generalists, with evidence for a high degree of metabolic flexibility [15].…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any mOTU encoding all the putative oxidation genes in the core genome (Figure 2 and 5). Metabolic flexibility is a key factor governing distributions of taxa across ecosystems (54). However, in this study we did not find a correlation between how widespread an mOTU is and their capacity to use different electron acceptors.…”
Section: The Metabolic Potential Of the Most Abundant Chlorobium Groupscontrasting
confidence: 79%
“…This agrees with recent reports that environmental and spatial drivers differentially act on common and rare taxa ( 77 , 78 ). Abundant generalists and rare specialists have been shown to differentially respond to environmental change, reflecting differences in niche breadth ( 11 , 79 , 80 ). Beyond these pairwise observations, we used zeta diversity to demonstrate that the turnover patterns reflect those typically observed in deterministically structured communities.…”
Section: Discussionmentioning
confidence: 99%